Mexican pregnant women show higher depression and anxiety with rising age and in the case of being single - Salgado, Irma Visoso; Mendoza, Jayson Leonel Moncada; Zerón, Hugo Mendieta (Acta medica Lituanica, 2020)
Background. Pregnancy is an important predisposition period to develop anxiety and depression, with a direct impact on the woman’s offspring. The aim of this study was to report the correlation between depression and anxiety in pregnant women and its association with the marital status and age. Materials. A descriptive, retrospective and cross-sectional study was conducted in the outpatient care of the Psychology Service at the “Mónica Pretelini Sáenz” Maternal Perinatal Hospital (HMPMPS), Toluca, Mexico, from June 2012 to March 2019. As routine, the Beck Depression Inventory (BDI-II) and the Beck Anxiety Inventory-Trait (BAIT), were applied to all women seeking attention at the HMPMPS. Only pregnant patients were selected for this study, with the women referred for the first time to the external Psychology Clinic as inclusion criteria. Pearson’s correlation coefficient and the frequency of cases for age, BDI-II, and BAIT were obtained using the IBM SPSS Statistics ® v.23 software. Results. The study included 2947 pregnant patients with a mean age of 28.6 ± 6.9 years. Of these, 2616 (88.8%) presented with mild anxiety, 269 (9.1%) with moderate, and 62 (2.1%) with severe anxiety. On the other hand, 2149 (72.9%) patients presented with minimal depression, 341 (11.6%) mild depression, 268 (9.1%) moderate depression, and 189 (6.4%) had severe depression. The correlations between age and BDI-II was –0.026 (P = 0.152), between age and BAI was –0.038 (P = 0.037), and between BAIT and BDI-II 0.650 (P ≤ 0.001). Conclusions. The age group with the highest frequency of depression and anxiety was from 20 to 29 years. The absence of a stable partner represented an important risk factor for anxiety and depression during pregnancy.